AtCOX17, an Arabidopsis Homolog of the Yeast Copper Chaperone COX17 - Balandin, Teresa (American Society of Plant Physiologists, 2002)
We have identified a new plant gene, AtCOX17, encoding a protein that shares sequence similarity to COX17, a Cu-binding protein from yeast (Saccharomyces cerevisiae) and vertebrates that mediates the delivery of Cu to the mitochondria for the assembly of a functional cytochrome oxidase complex. The newly characterized Arabidopsis protein has six Cys residues at positions corresponding to those known to coordinate Cu binding in the yeast homolog. Moreover, we show that the Arabidopsis COX17 cDNA complements a COX17 mutant of yeast restoring the respiratory deficiency associated with that mutation. These two lines of evidence indicate that the plant protein identified here is a functional equivalent of yeast COX17 and might serve as a Cu delivery protein for the plant mitochondria. COX17 was identified by investigating the hypersensitive response-like necrotic response provoked in tobacco (Nicotiana tabacum) leaves after harpin inoculation. AtCOX17 expression was activated by high concentrations of Cu, bacterial inoculation, salicylic acid treatment, and treatments that generated NO and hydrogen peroxide. All of the conditions inducing COX17 are known to inhibit mitochondrial respiration and to produce an increase of reactive oxygen species, suggesting that gene induction occurs in response to stress situations that interfere with mitochondrial function.